2021
DOI: 10.2196/28360
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health and the Perceived Usability of Digital Mental Health Tools Among Essential Workers and People Unemployed Due to COVID-19: Cross-sectional Survey Study

Abstract: Background COVID-19 has created serious mental health consequences for essential workers or people who have become unemployed as a result of the pandemic. Digital mental health tools have the potential to address this problem in a timely and efficient manner. Objective The purpose of this study was to document the extent of digital mental health tool (DMHT) use by essential workers and those unemployed due to COVID-19, including asking participants to r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 56 publications
3
9
0
Order By: Relevance
“…The participants consistently identified simplicity as a major design feature, but other common features included information, meditation or mindfulness tools, and links to other resources. This is extremely similar to popular features identified by unemployed individuals and essential workers for MHapps intended to support distress during the COVID-19 pandemic [64]. A few of our participants also noted distraction tools, which were also identified in the study [64], especially among unemployed workers.…”
Section: Reflections On the Apps That The Youth Designed In The Last ...supporting
confidence: 78%
See 1 more Smart Citation
“…The participants consistently identified simplicity as a major design feature, but other common features included information, meditation or mindfulness tools, and links to other resources. This is extremely similar to popular features identified by unemployed individuals and essential workers for MHapps intended to support distress during the COVID-19 pandemic [64]. A few of our participants also noted distraction tools, which were also identified in the study [64], especially among unemployed workers.…”
Section: Reflections On the Apps That The Youth Designed In The Last ...supporting
confidence: 78%
“…This is extremely similar to popular features identified by unemployed individuals and essential workers for MHapps intended to support distress during the COVID-19 pandemic [64]. A few of our participants also noted distraction tools, which were also identified in the study [64], especially among unemployed workers. However, these interests are somewhat inconsistent with common features within MHapps, with the finding that the most common features both alone and in combination are journaling and mood tracking [65].…”
Section: Reflections On the Apps That The Youth Designed In The Last ...supporting
confidence: 78%
“…This SUS score corresponds to being "good," as proposed by Bangor et al [38]. These findings are similar to other digital interventions addressing stress [39][40][41][42] and are encouraging, since Champion et al [42] found that improvements in stress can be achieved through short-term engagement (an average of six times) with a mindfulness-based cognitive therapy mobile app. Participants echoed some of the quantitative findings in the interviews, saying that the video game was easy to use, but mentioned a few functionality features that could be improved.…”
Section: Principal Findingssupporting
confidence: 78%
“…This barrier may be exacerbated in the D/HH community due to missed incidental learning opportunities about mental health. Furthermore, similar to previous work with hearing populations [ 31 ], participants valued immediate access to resources. Participants rated access to suicide prevention support and peer chat as one of the most important features to include in a mental health app, which resonates with work with other communities: a recent study with essential workers found that one of the most desired features for a mental health technology was the ability to chat with a mental health professional or peer, and a link to mental health resources and crisis support [ 31 ].…”
Section: Discussionmentioning
confidence: 56%